PENGARUH SOCIAL MEDIA MARKETING, INFLUENCER, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN MENGINAP DI HOTEL THE KAYON RESORT - Permatasari, Komang; Prawitasari, Putu Putri (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of social media marketing, influencers, and online customer reviews partially and simultaneously on the decision to stay. The sample in this study is 140 guests who stay at the Kayon Resort Hotel. The data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was obtained that social media marketing, influencers and online customer reviews have a significant effect on the decision to stay, social media marketing has a positive and significant effect on the decision to stay, influencers have a positive and significant effect on the decision to stay, and online customer reviews have a significant positive effect on the decision to stay. The magnitude of the influence of the independent variable on the decision to stay was 74.2%. The suggestion that the researcher can give is that The Kayon Resort Hotel should always be active in providing information The Kayon Resort should always create interesting content, so that later many consumers will comment on social media, in implementing promotions, collaborating with well-known influencers, always trying to make the tourists who stay satisfied, and always maintaining a good reputation, So that later consumers always give good reviews on various online platforms.